O ser-como-o-outro, a solidão e a morte em A Paixão sgundo G. H., de Clarice Lispector - Barankievicz, Ivana Vilane de Freitas (2016)
The human being was always faced with existential questions. As beings-in-the world, we share the same possibility of sensations and experiences. Many of these experiences generate in us the anxiety and solitude, as the death, once this experience ends every possibility of the being, the pendent of the presence. In this work, death and existential problems faced by two protagonists of Clarice Lispector are used in our analysis of the novel The Passion According to G.H. and the short story The Buffalo. We are based on the existential philosophy of Martin Heidegger (2003, 2012) and Octavio Paz (1976) and literature in works of Bosi (1985, 2001) and Libanori (2006), among others. Our aim is to observe and compare the existential themes presented in both texts from the hypothesis that both characters reveal the human anxiety of being. In our analysis, we observed that in both texts the characters are women who face existential dramas, marked by solitude and by the meeting with others in their lives. Since the experience of being-with-other, marked by the meeting of looks of the women with the animals, the protagonists recognized themselves as presence in a symbolic process of death. This death, in opposite of the physical one, transform these women, generating feelings of anxiety, hate, despite of the social attachments they were tied on. This self-diving reveals an authentic and deep process of death, self-knowledge and rediscovery of life.